Competing event risk stratification may improve the design and efficiency of clinical trials: Secondary analysis of SWOG 8794 - Zakeri, Kaveh (2012)
BACKGROUND: Composite endpoints can be problematic in the presence of competing risks when a treatment does not affect events comprising the endpoint equally. METHODS: We conducted secondary analysis of SWOG 8794 trial of adjuvant radiation therapy (RT) for high-risk post-operative prostate cancer. The primary outcome was metastasis-free survival (MFS), defined as time to first occurrence of metastasis or death from any cause (competing mortality (CM)). We developed separate risk scores for time to metastasis and CM using competing risks regression. We estimated treatment effects using Cox models adjusted for risk scores and identified an enriched subgroup of 75 patients at high risk of metastasis and low risk of CM. RESULTS: The mean CM risk score was significantly lower in the RT arm vs. control arm (p=0.001). The effect of RT on MFS (HR 0.70; 95% CI, 0.53–0.92; p=0.010) was attenuated when controlling for metastasis and CM risk (HR 0.76; 95% CI, 0.58–1.00; p=0.049), and the effect of RT on overall survival (HR 0.73; 95% CI, 0.55–0.96; p=0.02) was no longer significant when controlling for metastasis and CM risk (HR 0.80; 95% CI, 0.60–1.06; p=0.12). Compared to the whole sample, the enriched subgroup had the same 10-year incidence of MFS (40%; 95% CI, 22–57%), but a higher incidence of metastasis (30% (95% CI, 15–47%) vs. 20% (95% CI, 15–26%)). A randomized trial in the subgroup would have achieved 80% power with 56% less patients (313 vs. 709, respectively). CONCLUSION: Stratification on competing event risk may improve the efficiency of clinical trials.